Novel Nanomaterials 2021
DOI: 10.5772/intechopen.94348
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Metal Nanoparticles for Antimicrobial Activity

Abstract: The development and extensive spread of multi-drug resistant bacteria are considered as a major public health concern. Failures to control severe infections due to antibiotic resistance have augmented healthcare costs as well as patient morbidity and mortality. Presently, natural product-based therapeutics are gaining significant attention both for their antimicrobial effectiveness and for not persuading drug resistance. Furthermore, recent developments in nanoscience on new drug delivery systems built on nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 132 publications
(183 reference statements)
0
10
0
Order By: Relevance
“…The use of natural or biomolecular templates, on the other hand, eliminates the need for toxic chemicals in the synthesis, leading to the formation of biometal NPs with good biocompatibility and unique biofunctionalities (e.g., antiviral) as highlighted below. 31,34,38,39 2.1.1. DNA-Templated Synthesis.…”
Section: Biomimetic Synthesis Of Metalmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of natural or biomolecular templates, on the other hand, eliminates the need for toxic chemicals in the synthesis, leading to the formation of biometal NPs with good biocompatibility and unique biofunctionalities (e.g., antiviral) as highlighted below. 31,34,38,39 2.1.1. DNA-Templated Synthesis.…”
Section: Biomimetic Synthesis Of Metalmentioning
confidence: 99%
“…130 Therefore, a great deal of research has been conducted on how plants can be used as promising green biofactories to produce metal NPs. 34 Similar to the bacterial system, plants have diverse cell surveillance mechanisms that effectively detoxify the overconcentration of metallic cations. 156 Furthermore, it has been demonstrated that the as- synthesized metal NPs accumulate in some organelles of plant cells, such as vacuoles.…”
Section: Metallization Through Interaction With Phosphatementioning
confidence: 99%
See 3 more Smart Citations